2000
DOI: 10.1007/pl00010974
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dissimilatory metal reduction on fate of organic and metal contaminants in the subsurface

Abstract: Dissimilatory Fe(III)-reducing microorganisms have the ability to destroy organic contaminants under anaerobic conditions by oxidizing them to carbon dioxide. Some Fe(III)-reducing microorganisms can also reductively dechlorinate chlorinated contaminants. Fe(III)-reducing microorganisms can reduce a variety of contaminant metals and convert them from soluble forms to forms that are likely to be immobilized in the subsurface. Studies in petroleum-contaminated aquifers have demonstrated that Fe(III)-reducing mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(79 citation statements)
references
References 73 publications
(65 reference statements)
0
77
1
1
Order By: Relevance
“…Direct microbial (enzymatic) reduction coupled to oxidation of organic carbon and H 2 is recognized as the dominant mechanism for Fe(III) oxide reduction in nonsulfidogenic anaerobic soils and sediments (see Lovley 1991Lovley , 2000. This process contributes to both natural and contaminant (hydrocarbon) organic carbon oxidation in sedimentary environments, and exerts a broad range of impacts on the behavior of trace and contaminant metals and radionuclides (Lovley and Anderson 2000). Reduced sulfur (S) oxidation processes (both biotic and abiotic) drive much of Fe(III) oxide reduction in sulfur-rich marine sediments (e.g.…”
Section: Bacterial Fe Redox Cyclingmentioning
confidence: 99%
“…Direct microbial (enzymatic) reduction coupled to oxidation of organic carbon and H 2 is recognized as the dominant mechanism for Fe(III) oxide reduction in nonsulfidogenic anaerobic soils and sediments (see Lovley 1991Lovley , 2000. This process contributes to both natural and contaminant (hydrocarbon) organic carbon oxidation in sedimentary environments, and exerts a broad range of impacts on the behavior of trace and contaminant metals and radionuclides (Lovley and Anderson 2000). Reduced sulfur (S) oxidation processes (both biotic and abiotic) drive much of Fe(III) oxide reduction in sulfur-rich marine sediments (e.g.…”
Section: Bacterial Fe Redox Cyclingmentioning
confidence: 99%
“…The process has been extensively studied (Geomicrobiology, 2002;DiChristina et al, 2005;Kappler and Straub, 2005;Roden, 2006;Weber et al, 2006). Dissimilatory Fe(III) reduction influences system redox state and buffering capacity Komlos et al, 2007); the valence and composition of pore-water solutes Bennett et al, 1993); the identity, surface properties, and geochemical reactivity of the Fe-containing mineral fraction (e.g., Zachara et al, 2004;Plymale et al, 2011); and the chemical form, persistence, and fate of a wide range of inorganic and organic contaminants (Lovley and Anderson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies of their metabolism have revealed them to be capable of bioremediation of several heavy metals, including uranium, plutonium, technetium, and vanadium, as well as biodegradation of several organic contaminants, including monoaromatic hydrocarbons (16,17,26). More recently, Geobacter species have been used to generate electricity from waste organic matter (2,15,19). These unique metabolisms make Geobacter species important players in the contaminated subsurface environment (18).…”
mentioning
confidence: 99%